Sosialisasi dan Edukasi Digital Talent Management pada UMKM Keripik Singkong Alif di Desa Suka Damai - Dina Mellita; Andrian Noviardy; Efan Elpanso; Ahmad Abdillah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Keripik Singkong Alif, a micro-enterprise located in Suka Damai Village, faces challenges in managing human resources due to its traditional and unstructured operational system, leading to inefficiencies and obstacles in business development. To address this issue, socialization and education on Digital Talent Management (DTM) were conducted as a solution to improve HR management through a simple and applicable digital approach. This activity aimed to educate micro-business actors on the importance of talent management. The methods used included field observations, interviews, socialization, training, mentoring, and step-by-step evaluation to ensure that business owners could understand and independently implement the system. The results of the activity show that the socialization program consisted of several stages, namely observation, problem identification, implementation of socialization and education, and evaluation. Through four days of socialization and education, Keripik Singkong Alif successfully established a clearer division of tasks, recognized employee potential, and agreed on work procedures through the development of a simple Guidebook. The digital approach used effectively raised awareness among business owners about the importance of work documentation and performance evaluation, despite initial challenges in digital literacy.